Lightweight geopolymer made of highly porous siliceous materials with various Na2O/Al2O3and SiO2/Al2O3ratios - K. Pimraksa (2018)
The syntheses of lightweight geopolymeric materials from highly porous siliceous materials viz. diatomaceous earth (DE) and rice husk ash (RHA) with high starting SiO2/Al2O3ratios of 13.0-33.5 and Na2O/Al2O3ratios of 0.66-3.0 were studied. The effects of fineness and calcination temperature of DE, concentrations of NaOH and KOH, DE to RHA ratio; curing temperature and time on the mechanical properties and microstructures of the geopolymer pastes were investigated. The results indicated that the optimum calcination temperature of DE was 800°C. Increasing fineness of DE and starting Na2O/Al2O3ratio resulted in an increase in compressive strength of geopolymer paste. Geopolymer pastes activated with NaOH gave higher compressive strengths than those with KOH. The optimum curing temperature and time were 75°C and 5days. The lightweight geopolymer material with mean bulk density of 0.88g/cm3and compressive strength of 15kg/cm2was obtained. Incorporation of 40% RHA to increase starting SiO2/Al2O3and Na2O/Al2O3ratios to 22.5 and 1.7 and enhanced the compressive strength of geopolymer paste to 24kg/cm2with only a marginal increase of bulk density to 1.01g/cm3. However, the geopolymer materials with high Na2O/Al2O3(>1.5) were not stable in water submersion. © 2011 Elsevier B.V.